1977
DOI: 10.1104/pp.60.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Reactions of Nodulated Leguminous Plants

Abstract: The ATP-dependent evolution of H2 catalyzed by nitrogenase and the hydrogenase-catalyzed oxidation of H2 have been implicated as factors influencing the efficiency of energy utilization in the N2 fixtion proces. The effects of rhizobial strain and plant age on the H2-evolving and H2-utillzing activity of leguminous root nodules are described in this manuscript. Two dases of legume-Rhizobium combinations were observed in studies with soybeans (Glycine max L. Merr.) and cowpeas (Vigna unguiculate L. Walp.). One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…The levels of these three To examine the relationship between ureide synthesis, nitrogen fixation, and de novo purine biosynthesis, the relative rates of nitrogen export as ureides and estimated rates of nitrogen fixation and PRPP synthesis were compared (Fig 6). The rates of nitrogen fixation were estimated using a conversion factor of 2 C2H2 reduced per NH4+ produced based on relative efficiency measurements (29) for this combination of host cultivar and strain of R japonicum. The Comparison of the relative rates of ureide export, nitrogen fixation and PRPP synthesis during nodule development.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of these three To examine the relationship between ureide synthesis, nitrogen fixation, and de novo purine biosynthesis, the relative rates of nitrogen export as ureides and estimated rates of nitrogen fixation and PRPP synthesis were compared (Fig 6). The rates of nitrogen fixation were estimated using a conversion factor of 2 C2H2 reduced per NH4+ produced based on relative efficiency measurements (29) for this combination of host cultivar and strain of R japonicum. The Comparison of the relative rates of ureide export, nitrogen fixation and PRPP synthesis during nodule development.…”
Section: Resultsmentioning
confidence: 99%
“…Using 3H2 incorporation as an assay for uptake hydrogenase, they suggested that changes in RE ofthat host-strain combination resulted from variations in both uptake hydrogenase activity and EAC (4). In other studies of a symbiosis between the Hup+ Rhizobium strain 176A28 and Vigna unguiculata (L.) Walp., where essentially no H2 was measured outside the nodule, plant age had no effect on RE (18).…”
mentioning
confidence: 99%
“…However, symbiotic characteristics with these nonhomologous hosts have been investigated in detail with only few strains of A japonicum. Strain-dependent hydrogen evolution and hydrogenase activity by R. japonicum in symbiosis with soybean has been reported (18,19), but these characters have not been studied with other legumes as hosts. Our objectives were to investigate the legume host-A japonicum strain interactions for nodulation, effectiveness, acetylene reduction, hydrogen evolution, and hydrogenase activity in soybean, cowpea, and siratro.…”
Section: Introductionmentioning
confidence: 99%